Flavonol‐mediated stabilization of PIN efflux complexes regulates polar auxin transport - Teale, William D (EMBO J, 2020)
The transport of auxin controls the rate, direction and localization of plant growth and development. The course of auxin transport is defined by the polar subcellular localization of the PIN proteins, a family of auxin efflux transporters. However, little is known about the composition and regulation of the PIN protein complex. Here, using blue‐native PAGE and quantitative mass spectrometry, we identify native PIN core transport units as homo‐ and heteromers assembled from PIN1, PIN2, PIN3, PIN4 and PIN7 subunits only. Furthermore, we show that endogenous flavonols stabilize PIN dimers to regulate auxin efflux in the same way as does the auxin transport inhibitor 1‐naphthylphthalamic acid (NPA). This inhibitory mechanism is counteracted both by the natural auxin indole‐3‐acetic acid and by phosphomimetic amino acids introduced into the PIN1 cytoplasmic domain. Our results lend mechanistic insights into an endogenous control mechanism which regulates PIN function and opens the way for a deeper understanding of the protein environment and regulation of the polar auxin transport complex.